Experiments in Egyptian archaeology - Stocks, Denys A. (Denys Allen), 1941- author.
1 online resource
Keywords: "In this new edition of Experiments in Egyptian Archaeology Denys A. Stocks introduces further experimental research on stoneworking in Ancient Egypt through archaeological and pictorial evidence. A further 20 years of research has been added to the original publication and the book now includes the results of experiments that test and evaluate over two hundred and fifty reconstructed and replica tools, bringing alive the methods and practices of ancient Egyptian craftworking. This practical approach to understanding the fundamentals of ancient Egyptian stoneworking highlights the evolution of tools and techniques, and how these come together to produce the wonders of Egyptian art and architecture. A new chapter on predynastic industrial transitions and convergence explores how the surge in technology, particularly in the expanding production of stone vessels and in the production of faience artefacts, drove the expansion of the economy of the Late Predynastic period in Egypt. Introducing the results of new research to enrich our understanding of the fundamental development of stoneworking, and other, supporting technologies, in Ancient Egypt, this book remains an important volume for students and researchers wishing to understand Ancient Egyptian technology and development"--